Level of Organizational Commitment of Employees of the Propaganda and Training Department in Phongsaly Province - Singchao, Phonexay; DUANGVILAYKEO, Thipphavanh; SITHIRAJVONGSA, Vilat; OUNPHOUVONG4, Stamy (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aims to assess the level of organizational commitment among employees of the Phongsaly Provincial Propaganda and Training Department. The target group includes all 66 employees, and a questionnaire was used as the primary data collection tool. Data were analyzed by using SPSS statistical software. The results indicated that overall organizational commitment among employees was moderate, with a mean value of 3.02 (SD = 0.20). Several aspects were examined in more detail, revealing varying levels of commitment. The highest levels of commitment were found in aspects such as equality within the organization (mean = 4.31, SD = 0.46) and justice within the organization (mean = 3.92, SD = 0.66). Employees also reported relatively high commitment to having the autonomy to plan their actions (mean = 3.87, SD = 0.88) and using their knowledge and abilities in their work (mean = 3.81, SD = 0.95). Other positive aspects included mutual respect (mean = 3.77, SD = 0.42) and achieving personal work goals (mean = 3.54, SD = 0.91). However, several areas revealed lower levels of organizational commitment. These included passion for one's career (mean = 3.46, SD = 0.94), job suitability to professional knowledge (mean = 3.24, SD = 1.15), and solidarity and support within the organization (mean = 3.03, SD = 0.84). Moreover, aspects such as mutual encouragement, punctuality, opportunities for professional development, and satisfaction with office welfare policies all showed lower commitment levels, with mean values ranging from 2.00 to 2.93 and standard deviations between 0.74 and 0.95. These results suggest that while employees feel moderately committed to their organization, there are areas